2020
DOI: 10.1002/oby.22992
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Probability of Purchasing Moderately Sugary Beverages and 100% Fruit Juice Vary Across Sugar Tax Structures?

Abstract: Objective Sugar‐sweetened beverage taxes are increasingly used to discourage sugar intake; however, the impact on consumer preferences for particular products is largely unknown. This study explored the impact of two tax structures (tiered vs. nontiered and inclusive vs. exclusive of 100% fruit juice) on participants’ probability of purchasing moderately sugary beverages and 100% fruit juice. Methods A sample of 3,584 Canadians aged 13 years and older completed a series of beverage purchasing tasks, each corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(27 reference statements)
1
0
0
Order By: Relevance
“…These results, consistent with other work [ 37 ], aligns with the policy discussions regarding the best ways to use SSB revenues, as subsidies for healthy alternatives such as fruits and vegetables are frequently mentioned. One simulation study found that the tax burden of the poor would be mitigated by such an option, although it also noted that nutritional intake might not differ substantively [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results, consistent with other work [ 37 ], aligns with the policy discussions regarding the best ways to use SSB revenues, as subsidies for healthy alternatives such as fruits and vegetables are frequently mentioned. One simulation study found that the tax burden of the poor would be mitigated by such an option, although it also noted that nutritional intake might not differ substantively [ 38 ].…”
Section: Discussionsupporting
confidence: 92%